2013
DOI: 10.7860/jcdr/2013/5375.3140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Trichomonas Vaginalis Infection in A Tertiary Care Hospital in Rural Bangalore, Southern India

Abstract: Background: The infection with Trichomonas vaginalis is one of the most common sexually transmitted diseases (STDs) in humans. The prevalence of this infection has been reported to be between 2 to 8%, depending on the different socio-cultural conditions. This study aimed to determine the prevalence of T. vaginalis in the women who were referred to the gynaecologic clinics at the MVJ medical college, Bangalore, India.Methods: This descriptive, cross-sectional study was conducted on 750 women who were referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(2 reference statements)
4
3
0
Order By: Relevance
“…[ 10 ] Even higher prevalence between 6.1% and 8.6% has been reported from Punjab[ 11 ] and some parts of South India (Tamil Nadu and Karnataka) between 2005 and 2013. [ 12 13 14 ] Lower prevalence comparable to the present study has also been reported from Bangaluru, Karnataka(2.1%),[ 15 ] Gujarat (2.8%),[ 16 ] and Maharashtra (3.3%). [ 17 ]…”
Section: Discussionsupporting
confidence: 85%
“…[ 10 ] Even higher prevalence between 6.1% and 8.6% has been reported from Punjab[ 11 ] and some parts of South India (Tamil Nadu and Karnataka) between 2005 and 2013. [ 12 13 14 ] Lower prevalence comparable to the present study has also been reported from Bangaluru, Karnataka(2.1%),[ 15 ] Gujarat (2.8%),[ 16 ] and Maharashtra (3.3%). [ 17 ]…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of this infection has been reported to be between 2% and 8%, depending on the different sociocultural conditions. [7] The overall prevalence of trichomoniasis in the study group was 2.9% which correlates with 2.1% of Vijaya Mn et al . study who studied the prevalence of T. vaginalis infection in rural Bengaluru.…”
Section: Discussionsupporting
confidence: 75%
“…[7] Vaginal discharge is a common health problem among women in the reproductive age. It is usually neglected by women making the diagnosis more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study showed that the sensitivity, specificity, and positive and negative predictive values of the clinical diagnosis compared with those of the culture method for T. vaginalis were 75%, 95%, 28%, and 99%, respectively [ 19 ]. Interestingly a high prevalence of (40%) trichomoniasis was reported among women in [ 20 ] Zambia, even among women who had never had sex [ 19 ].…”
Section: Discussionmentioning
confidence: 99%